The fossil record of the asteroid (Echinodermata) family Chaetasteridae Sladen, 1889 and subfamily Hyalothricinae Fisher, 1911 - Gale, Andrew S. (Zootaxa, 2020)
The Cretaceous asteroid Arthraster is referred to the living family Chaetasteridae on the basis of similarities in ossicular arrangement in the abactinal disc and arms. Chaetasterina, previously identified as a chaetasterid, is transferred to the family Asterinidae, subfamily Hyalothricinae, and constitutes the first fossil record of the subfamily.